Productivity of logging large diameter logs and long logs during final cutting in a mountain forest in Japan. Issue 3 (2nd September 2019) - Nakazawa, Masahiko; Yoshida, Chikashi; Sasaki, Tatsuya; Taki, Seishiro; Uemura, Takumi; Ito, Takayuki; Yamaguchi, Hirokazu; Mozuna, Masahiro; Usui, Kengo; Inomata, Yuta; Suzuki, Hidenori; Yamaguchi, Satoshi; et al.
ABSTRACT: A large portion of planted forests in Japan have recently reached maturity. These trees have grown larger than previous stands, and are more difficult to log using current techniques. This study aimed to develop an improved logging system for logs with relatively larger diameters and lengths in Japan. In a moderate-slope mountain forest in Toyama Prefecture, we evaluated the productivity of final cutting and compared the productivity of each log length class (4 m, 6 m, and 8 m) using both current-sized and larger-sized machine harvesting systems. Moreover, different felling techniques for large diameter trees were assessed using a mechanical wedge that is commonly used in central Europe. We found that felling using the mechanical wedge had additional safety benefits. Furthermore, the productivity using the larger machine system was higher than those using the current techniques and systems; however, the productivity was only marginally higher for larger machines across log length classes.